2015
DOI: 10.1142/s1363919615500383
|View full text |Cite
|
Sign up to set email alerts
|

Service Innovation Performance and Information Technology: An Empirical Analysis From the Dynamic Capability Perspective

Abstract: Service firms need to continuously innovate their service offerings in order to remain competitive in constantly changing market conditions. Successful innovators utilise current information technology (IT) to access service innovation capacity and knowledge which can be located internal or external to their organisation. In this paper, we develop and test a theoretical framework that explains how IT can contribute to service innovation performance, and finally, to service provision performance. Drawing on dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 78 publications
1
26
0
Order By: Relevance
“…This is sometimes referred to as capabilities that include 'sensing' and 'seizing' as well as reconfiguring or 'transforming'. (Castiaux, 2012;Plattfaut et al, 2015). Lawson and Samson (2001) have proposed an innovation capability construct at the firm level that includes seven elements: vision and strategy, harnessing competencies, organisational intelligence, creativity, organisational structures, culture and the management of technology.…”
Section: Dynamic Capabilities and Innovationmentioning
confidence: 99%
“…This is sometimes referred to as capabilities that include 'sensing' and 'seizing' as well as reconfiguring or 'transforming'. (Castiaux, 2012;Plattfaut et al, 2015). Lawson and Samson (2001) have proposed an innovation capability construct at the firm level that includes seven elements: vision and strategy, harnessing competencies, organisational intelligence, creativity, organisational structures, culture and the management of technology.…”
Section: Dynamic Capabilities and Innovationmentioning
confidence: 99%
“…The deep involvement of customers, employees, and service network partners impose significant demands on the organization to generate, process, and distribute information between and together with diverse stakeholders (e.g., Nijssen, Hillebrand, Vermeulen, and Kemp, ; Storey, Cankurtaran, Papastathopoulou, and Hultink, ; Wieland, Polese, Vargo, and Lusch, ). Regarding the use of IT tools, previous research has emphasized their importance for service innovations (e.g., Plattfaut et al, ), but has also identified several challenges, due to the heterogeneity of the stakeholders (Jaakkola, Meiren, Witell, and Reynoso, ). This implies that the use of IT and its performance impact cannot be independent from the firm's business focus.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting finding is that a considerable amount of the select articles (14 out of 42) aim to measure the influence of DCs on some aspect of organization performance – i.e. portfolio performance (Biedenbach and Müller, 2012), customer-oriented organizational performance (Desai et al , 2007), innovation performance (Plattfaut et al , 2015). Even though some argue that the relationship between DCs and organizational performance is difficult to measure (Easterby-Smith et al , 2009), we could observe an increasing interest of researchers on investigating this perspective of DCs.…”
Section: Resultsmentioning
confidence: 99%